The Making of Patty Slices by using High Protein Content Flour with Stabilizer Addition - Beby Yunita; Herla Rusmarilin; Terip Karo-Karo (Universitas Sumatera Utara, 2015)
The aim of this research was to find the effect of gum arabic stabilizer addition on the quality of patty slices. The research was conducted in two phases. 1) The manufacture of composite flour was made from mackerel fish flour and soybean flour (P) (100%:0%, 90%:10%, 80%:20%,70%:30%) with the addition of 10% tapioca. The flour was tested on moisture content, ash content, fat content, protein content, carbohidrat content, crude fiber content, water absorption, and oil absorption. 2) The manufacture of patty slices from the best ratio camposite flour of phase 1 by using stabilizer addition gum Arabic (F) (0,8%, 0,9%, 1,0%, and 1,1%), then proximate analysis, total microbial, texture (tenderness), water holding capacity, and organoleptic (value of colour, flavour, taste, dan texture) of patty slices were analyzed. Patty slices was made from the best ratio of mackerel fish flour and soybean flour of 70%:30%. Patty slices by using concentration of gum arabic had highly significant effect on moisture content, ash content, protein content, crude fiber content, texture (tenderness), total microbial, and water holding capacity. The best concentration of gum arabic of the patty slices was 1,1% Keywords: Flour, patty slices, stabilizer